Specialized second-opinion radiology review of PET/CT examinations for patients with diffuse large B-cell lymphoma impacts patient care and management. Issue 51 (December 2017) - Sawan, Peter; Rebeiz, Karim; Schoder, Heiko; Batlevi, Connie; Moskowitz, Alison; Ulaner, Gary A.; Dunphy, Mark; Mannelli, Lorenzo
Abstract : Abstract: To identify discrepancies in fludeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) reports generated by general radiologists and subspecialized oncological radiologists for patients with diffuse large B-cell lymphoma (DLBCL), and to assess if such discrepancies impact patient management. Two radiologists retrospectively reviewed 72 PET/CT scans of patients with DLBCL referred to our institutions between 2009 and 2011, and recorded the discrepancies between the outside and second-opinion reports regarding multiple preset criteria using kappa statistic ( Κ ), including the disease stage. A multidisciplinary staging that considered all patient clinical data, pathology, and follow up radiological scans, was considered as standard of reference. A hemato-oncologist, blinded to the reports' origin, subjectively graded the quality and structure of these reports for each patient to determine if clinical stage and disease activity could be derived accurately from these reports. Agreement was not, or slightly, achieved between the reports regarding the binary and multilevel criteria ( Κ  < 0–0.2 and weighted Κ  = 0.082, respectively). Second-opinion reviews of PET/CT scans were concordant with the multidisciplinary staging in 78% of cases with an almost perfect agreement ( Κ  = 0.860). A change in staging was demonstrated in 36% of cases. In addition, 68% of second-opinion reports were assigned the highest grades on quality (grades 4 and 5) by the hemato-oncologist, compared with 15% of outside reports, with no noted agreement (weighted Κ  = –0.007). Second-opinion review of PET/CT scans by sub-specialized oncological radiologists increases accuracy of initial staging, posttreatment evaluation and also the clinical relevance of the radiology reports.